(untitled) (Polish Yearbook of International Law, 2023)
The Russian aggression against Ukraine is heavily influenced by the memory of World War II (WWII), used by the Russian Federation as a consolidation tool to mobilise Russian society for the fight against a “neo-Nazi Ukraine”. Since 2014 Russia has adopted a set of legislative initiatives aiming to preserve a government-prescribed narrative about the exceptionally heroic role of the USSR in WWII and prohibiting any other interpretation under the threat of criminal and administrative sanctions. Both laws are using the decision of the International Military Tribunal (IMT) as a reference point to justify and legally substantiate such an interpretation, as the USSR was one of “victorious” nations which rendered justice against the Nazis in 1946. This article aims to show how the IMT rulings have been turned into an instrument of Russian propaganda and which lessons can be learned for the future of international tribunals, as well as examines the overall Ukrainian quest for Russian accountability.